SOCIO-PHILOSOPHIC ANALYSIS OF POLITICAL CONSCIOUSNESS PHENOMENON AS THE FORM OF REFLECTION OF POLITICAL COMMUNICATION PRACTICE - Харченко, Ю. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
In the article on the basis of socio-philosophic analysis the dialectical connection of political consciousness and political communication is defined.